Corporate governance regulation : how poor management is destroying the global economy - Vakkur, Nicholas V. (John Wiley & Sons, 2013)
"Modern history persuasively demonstrates the inexorable link that binds comprehensive regulation to the global economy. This important book, rather than simply recount a litany of corporate governance failures, persuasively explains why, despite policymakers' best intentions, regulation has failed in the modern era. An objective study intended for a diverse readership, Corporate Governance Regulation unveils the underlying, root causes of regulatory failure."--Publisher's website.